NAVIGATING THE CHALLENGES OF TRANSCATHETER AORTIC VALVE REPLACEMENT (TAVR): A CASE STUDY - Tushar Menon, MD (Elsevier, 2024)
Therapeutic Area: Other: CV Surgery Case Presentation: A 66-year-old man presented with severe symptomatic bicuspid aortic stenosis and New York Heart Association class III chronic diastolic congestive heart failure. Despite being evaluated by the heart team and considering surgical aortic valve replacement, he opted for TAVR. During his procedure, severe annular and leaflet calcification complicated the valve deployment, leading to valve migration and necessitated emergent retrieval and repositioning. Post-procedure, the patient developed hypotension and tamponade physiology, prompting emergent pericardiocentesis. Subsequently, an acute type A aortic dissection was discovered, mandating open aortic valve replacement with ascending aortic graft. Background: The decision-making process in TAVR involves weighing individual patient factors against procedural risks, underscoring the need for shared decision-making and comprehensive preoperative evaluation.The significant challenge posed by severe valve calcification, which resulted in valve migration, emphasizes the importance of intraoperative imaging for real-time visualization during transcatheter aortic valve replacement (TAVR) procedures. These imaging modalities, such as transesophageal echocardiography (TEE) or intravascular ultrasound (IVUS), enable precise assessment of anatomical structures and guide the deployment of the valve with optimal positioning. Additionally, skilled intervention is essential in navigating procedural complexities encountered during TAVR. Experienced interventionalists, as in this case, possess the expertise to address challenges promptly, such as managing calcified anatomy or addressing complications like valve migration.The development of cardiac tamponade highlights the necessity for vigilant post-procedural monitoring and prompt intervention. Timely recognition and management of complications is critical in optimizing patient outcomes. Furthermore, the discovery of an acute type A aortic dissection emphasizes the potential for catastrophic events in TAVR recipients. This case highlights the importance of maintaining a high index of suspicion for procedural complications and the readiness to escalate to open surgical intervention when necessary. Conclusions: Transcatheter aortic valve replacement (TAVR) has emerged as a viable option for select patients with severe aortic stenosis, particularly those deemed too high risk for surgical intervention. However TAVR it is not without complications, as demonstrated in our case of a 66-year-old man who underwent TAVR but encountered significant perioperative and postoperative complications.